DESCOMPOSICIÓN Y CICLO DE NUTRIENTES EN ECOSISTEMAS TERRESTRES DE MÉXICO - Álvarez Sánchez, Javier (Instituto de Ecología, A.C., 2001)
Decumposition is one of the most important ecosystem processes. It implies the transformation of organic matter to more simple Chemical elements. The steps of this process are: comminution, leaching, mineralization and humification, which in tum aro regulated by climate, physicol soil properties, Chemical quality of decomposing material and the activities of docomposer biota. Actual evapotranspiration, lignin contcnts and C and N contents have been used to describe and predict temporal patterns. In México this process has been analyzed m several kinds of ccosystems, from grassiands to tropical forests. The mam approach has been the experimental analysis of leaf decomposuion, although m two studies wood was the analyzed substrato, Oniy in two other studies some groups of the decomposer fauna were descríbed. Finaliy, the ímportance of decomposer biota diversity and food webs is discussed. Consequently it is proposed to inelude in fulure studies more about díecomposing biota, food webs and the influence of decomposition in the carbón cycle and in the availability ot soil nutnents.